Desistance in drug-using offenders: a narrative review - Roeyen, Sofie Van (European journal of criminology, 2018)
The majority of available desistance research has examined desistance in the general offender population. However, applying the desistance approach to specific groups of offenders has potential to enrich our knowledge since their change processes show differences compared with those of the general offender population. Drug-using offenders is the group of offenders that has received most attention from desistance researchers. This article presents a narrative review of 15 studies that focus on desistance in this population. This review opted for a strict interpretation of ‘drug-using offenders’ in which two constitutive elements had to be present for inclusion, namely drug use and offending. Results indicate that only a limited amount of research applies the language of desistance to drug-using offenders. Also, it was apparent from the review that drug-using offenders are approached interchangeably with ‘desistance’ language and ‘recovery’ language. This review thus identifies gaps within the existing desistance literature, and it is expected that the further application of desistance language to drug-using offenders can build a better understanding of why and how drug-using offenders desist from drug use and offending. Further interdisciplinary research should be conducted on specific offender populations to improve understanding of the change process(es), which seems to be dual in nature but with a dynamic interplay between desistance and recovery.